Hydrological drought in the lower reaches of the Yangtze River (China): a 70-year data analysis - Hua Ge; Hua Ge; Lingling Zhu; Bing Mao; Bing Mao (Frontiers in Marine Science)
The combined impact of climate change and human activity has brought uncertainty regarding hydrological drought in the lower reaches of the Yangtze River (LYR), thereby threatening the security of regional water resources. To address this uncertainty, based on data from over 70 years, the trends, mutations, and causes of hydrological drought in the LYR were analyzed using the Mann–Kendall test method. The results of this study show that the most extreme annual hydrological drought situation defined by the daily minimum value improved, but the scenario defined by the monthly average intensified in September and October after the flood season, with a mutation in the 2000s after the Three Gorges Reservoir. The continuous decline in water availability during the flood season and the water storage of reservoirs after flooding made 2022 the most severe drought period in nearly 70 years. The rapid storage of reservoirs after flooding has promoted hydrological droughts in the LYR. In future scenarios, the impact of riverbed cutting on hydrological drought should be comprehensively evaluated, and the effects of future tide level changes under global climate change conditions should be measured.